Perception and Knowledge of Chronic Kidney Disease (CKD) among Undergraduate Students of Institut Supérieur Bilingue Libre du Togo (IBLT University Togo) - Imran, Tesleem Omotayo; Okunoye, Oyinkansola Sandara; Oduneye, Oluwalonimi Sharon; Olasupo, Faruq Olatunji (The Indonesian Institute of Science and Technology Research, 2025)
Chronic Kidney Disease (CKD) is a global health concern with increasing prevalence, particularly in developing countries. Despite its significant impact, public awareness and understanding of CKD remain limited. This study assessed the knowledge and perception of CKD among university students of IBLT University in Togo. A descriptive cross-sectional design was employed, and a standardized questionnaire was administered to 112 students, covering sociodemographic characteristics, CKD knowledge, and perception. The study found that while most students had a reasonable understanding of basic CKD concepts, significant gaps existed in their knowledge. Only 26% demonstrated good knowledge of CKD, while 46% had average knowledge and 28% exhibited poor knowledge. The perception of CKD varied among respondents. The majority believed that a person could live with one kidney, but there was uncertainty about screening costs and personal health awareness. Concerns about stigmatization, treatment costs, and religious beliefs were also prevalent. The study highlights the need for improved CKD education and awareness among young populations like university students. Targeted interventions are necessary to address knowledge gaps, dispel misconceptions, and provide support for individuals with CKD.